Fair trade: Making the marketplace mobile - Bartlett, Sarah (Technical Centre for Agricultural and Rural Cooperation, 2008)
Through web pages and text messages TradeNet allows rural farmers to advertise their merchandise to an international market and fi nd the fairest price for their crops.